Inhibitors of BMP‐1/tolloid‐like proteinases: efficacy, selectivity and cellular toxicity - Maya Talantikite; Pascaline Lécorché; Fabrice Beau; Odile Damour; Christoph Becker‐Pauly; Wen‐Bin Ho; Vincent Dive; Sandrine Vadon‐Le Goff; Catherine Moali (FEBS Open Bio, 2018)
BMP‐1/tolloid‐like proteinases belong to the astacin family of human metalloproteinases, together with meprins and ovastacin. They represent promising targets to treat or prevent a wide range of diseases such as fibrotic disorders or cancer. However, the study of their pathophysiological roles is still impaired by the lack of well‐characterized inhibitors and the questions that remain regarding their selectivity and in vivo efficiency. As a first step towards the identification of suitable tools to be used in functional studies, we have undertaken a systematic comparison of seven molecules known to affect the proteolytic activity of human astacins including three hydroxamates (FG‐2575, UK383,367, S33A), the protein sizzled, a new phosphinic inhibitor (RXP‐1001) and broad‐spectrum protease inhibitors (GM6001, actinonin). Their efficacy in vitro, their cellular toxicity and efficacy in cell cultures were thoroughly characterized. We found that these molecules display very different potency and selectivity profiles, with hydroxamate FG‐2575 and the protein sizzled being very powerful and selective inhibitors of BMP‐1, whereas phosphinic peptide RXP‐1001 behaves as a broad‐spectrum inhibitor of astacins. Their use should therefore be carefully considered in agreement with the aim of the study to avoid result misinterpretation.